Development of an improved acm scheme for mitigating earth-to-space propagation effects - Tekanyi, A. M. S.; Idris, R. M.; Usman, A. D.; Abdullahi , Z. M.; Agbon, E. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
In satellite communications, the communication link experiences propagation losses such as: Path loss, atmospheric losses, rain fading, ionosphere effects (such as scintillation), and other effects which can greatly affect the received signal strength and close the link budget in the worst case. The design of future broadband satellite systems has to be done with the challenge of more complex traffic mix and these harsher propagation conditions which mitigate the performance of the communications link. Link adaptation (LA) has been used in satellite communications applications for evaluating the performance of an adaptive modulation system in the unique space-based propagation environment. Despite the current research on improving satellite system performance, there is still a need to further develop a scheme that mitigates the effect of atmospheric impairments. This work develops an improved adaptive coding and modulation scheme that mitigates earth-to-space propagation effects. The scheme targets maximizing data throughput while staying below a Bit Error Rate (BER) threshold so as to successfully mitigate link impairment in fixed communication systems. Simulation of the work is carried out using MATLAB 2016b and System Toolkit (STK) 11.3. Simulation result showed that the iACM scheme was able to reduce the effect of path loss in time by 5% over the ACM scheme and also reduced the effect of path loss with respect to the angle of elevation by 2% over the ACM scheme and improvement in the network energy to noise ratio by 22.74% over ACM. In terms of system throughput, the iACM scheme showed an improvement in throughput by 24% over the ACM scheme. Finally, the iACM scheme has shown better performance in terms of throughput and thus, improve the performance of satellite communication.